Cover Image, Volume 15, Issue 3. Issue 3 (16th September 2021) - Unknown
Abstract : On the cover : Grower Ed Rose in his field of Lightning barley. See P. Hayes et al., "Registration of 'Lightning' barley, ' https://doi.org/10.1002/plr2.20129 . Photo by Pat Hayes.